2008
DOI: 10.1016/j.ygcen.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in CRF-I and urotensin I transcript levels in masu salmon: Correlation with cortisol secretion during spawning

Abstract: Pacific salmon employ a semelparous reproductive strategy where sexual maturation is followed by rapid senescence and death. Cortisol overproduction has been implicated as the central physiologic event responsible for the post-spawning demise of these fish. Cortisol homeostasis is regulated through the action of hormones of the hypothalamus-pituitary-interrenal (HPI) axis. These include corticotropin-releasing factor (CRF) and urotensin-I (UI). In the present study, masu salmon (Oncorhynchus masou) were assaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 62 publications
0
18
0
2
Order By: Relevance
“…In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011). In fact, plasma cortisol levels can reach several hundred ng/ml and remain elevated for weeks to months in sexually mature and migrating Pacific salmon (Carruth et al 2000, Hinch et al 2006, Westring et al 2008. As such, our findings contribute to our understanding of the mechanisms underlying the dynamic changes in food intake, growth and energy mobilization that characterize various chronic stressors and life history transitions.…”
Section: Discussionmentioning
confidence: 99%
“…In salmonids, sustained increases in cortisol levels are also associated with social subordination (Gilmour et al 2005) and with specific phases of the life cycle such as smolting (Nilsen et al 2008) and sexual maturation (Fuzzen et al 2011). In fact, plasma cortisol levels can reach several hundred ng/ml and remain elevated for weeks to months in sexually mature and migrating Pacific salmon (Carruth et al 2000, Hinch et al 2006, Westring et al 2008. As such, our findings contribute to our understanding of the mechanisms underlying the dynamic changes in food intake, growth and energy mobilization that characterize various chronic stressors and life history transitions.…”
Section: Discussionmentioning
confidence: 99%
“…salmonid fishes is to be anticipated in light of the relatively high maternal plasma levels of cortisol in these species (ranging from 140 to 650 ng/ml) during the critical late stages of ovarian maturation (Morrison et al 1985, Kubokawa et al 1999, Carruth et al 2000, Westring et al 2008, McConnachie et al 2012. While the maternal total cortisol concentrations during gonadal maturation are somewhat lower for non-migratory oncorhynchid salmonids, such as rainbow trout (20-70 ng/ml) (Bry 1985, Caldwell et al 1991, Koldjaer et al 2004, w45% of that steroid is in the form of unconjugated hormone (Caldwell et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, these deleterious effects are associated with prolonged stimuli of aggressive agents resulting in high levels of plasma cortisol (Bayunova et al, 2002;Schreck, 2010). In animals at the final stages of the reproductive cycle, stress appears to have a positive effect on reproduction (Small, 2004;Westring et al, 2008;Milla et al, 2009). Previous studies have found that this effect may be observed especially in females, where treatment with corticosteroids (cortisol, 11-deoxycortisol, 11-deoxycorticosterona) induces ovulation in various fish species (Goetz & Theofan, 1979;Haider & Rao, 1994;Milla et al, 2009).…”
Section: Discussionmentioning
confidence: 99%